Removal of cadmium and lead from a mining effluent in Ticapampa- Recuay, Ancash using Serratia marcescens M8a-2T dry biomass - Alegre Quijano, Antori (2021)
The Ticapampa mining effluent was treated with Serratia marcescens M8a-2T dry biomass to remove polutants such as cadmium and lead. Response Surface Methodology (RSM) and Box–Behnken design matrix have been applied to optimizate the process. The influence of pH (2, 3 and 4), biomass concentration (1, 2 and 3 mg/mL) and contact time (15, 30 and 45 minutes) were evaluated. The maximum removal percentage for cadmium was 97.11% at pH 4, 2 mg/mL of biomass during 45 minutes; and for lead was 98.63% at pH 4, 1 mg/mL of biomass during 30 minutes. The high levels of significance (p <0.05) of the regression and ANOVA models indicated pH as the most influencer factor. The Response Surface Methodology was a very important tool to optimize bioremediation process.